EFEKTIVITAS PARTISIPASI MASYARAKAT DALAM PENYUSUNAN PROGRAM LEGISLASI DAERAH DI LINGKUNGAN PEMERINTAH KOTA BATU - Rina Rahayu; Bambang Santoso Haryono; Lely Indah Mindarti (Universitas Tribhuwana Tunggadewi, 2015)
The purpose of research is to describe, to identify, and analyze the community participation, the effectiveness of community participation, and factors supporting and inhibiting factors effectiveness of community participation in the preparation of Local Legislation Program in the Government Environment Batu City. The research uses a qualitative descriptive approach. Data were analyzed using interactive model Miles and Huberman.The results showed that community participation is Mobilized (forced or directed), and on the medium level of participation. Based on the process of analysis and policy formulation steady and careful planning, community participation had been effective. Factors supporting the effectiveness of community participation are: 1) the central government's policy; 2) the budget; 3) the enthusiasm of people; and 4) the cooperation with the consultant. Factors inhibiting the effectiveness of community participation are 1) budgetary constraints; 2) human resources are inadequate; 3) the low level of knowledge and understanding of society; and 4) the lack of media to access information for the community about local legislation draft.